Pola Komunikasi Virtual dalam Percakapan Tim Game Online Counter Strike - Yonatan Trianto (Jurnal Spektrum Komunikasi, 2018)
Online game Counter Strike: Global Offensive is an online game that provides communication features in it. Communication that occurs inside a virtual communication can be defined as, where the players get the ease of communicating for a good partnership. This research to find out how a virtual communication patterns that occur in conversations in drawing up the strategy team. This research uses the theory of virtual communication, communication patterns, computer mediated communication and the form of the interaction process to summarize and analyze findings data from interviews and observations.The results obtained indicate the existence of a multidirectional communication patterns formed from the activities of communication within the team. The form of the interaction process were also influential in the effectiveness of communication within the team.